Implementasi Sikap Religiusitas dalam Menunjang Keberhasilan Pembelajaran Anak Melalui Program Tahfidz Juz’amma di Taman Kanak-Kanak - Shidqiyah (GHULAMUNA: JOURNAL OF EARLY CHILDHOOD EDUCATION, 2023)
Instilling religious attitudes in schools since early childhood or kindergarten is also quite urgent, especially in the current era of digitalization where the culture of using mobile phones is increasingly widespread among children without intense control from the family. This study aims to examine how the implementation of success strategies for children's learning through the tahfidz program or memorizing letters in jus'amma at the Annuqayah Islamic Boarding School Kindergarten institution. As well as whether the application of the method succeeded in influencing the morale of the child or vice versa. To get valid results, the researchers used qualitative methods with data collection techniques through interviews, observation, and documentation. The results of the study conducted by the researchers found several urgent things, that the strategy of instilling religious attitudes in children was implemented by instilling religious knowledge, moral values ​​in activities implemented in kindergarten. For example, basic education in monotheism, moral values ​​education, the basics of religious practices, learning tahfidz juz'amma, instilling religious awareness in daily life, namely giving punishment with elements of religiosity, religious knowledge to be applied in life, habituation from an early age related to how to become a devout and moral Muslim, this is an optimal capital for the development of children's education.